Perbedaan Status Gizi, Pola Makan, Riwayat Diare, dan Pengetahuan Gizi Seimbang pada Anak Autisme dan Non-Autisme di Jakarta: Differences Nutritional Status, Dietary Patterns, Diarrhea History, and Nutritional Knowledge between Children with Autism and children without Autism in Jakarta - Aulia, Andini Rizky; Simanungkalit, Sintha Fransiske; Arini, Firlia Ayu (Amerta Nutrition, 2024)
Background: Autism Spectrum Disorder (ASD) is characterized by difficulties in social interaction and communication. Children with ASD are at risk of being overweight due to selective eating patterns and parents' lack of nutritional knowledge, and they often experience diarrhea due to enzyme deficiencies. Objectives: This study aims to determine the differences in nutritional status, dietary patterns, and diarrhea history between children with ASD and children without ASD, as well as the differences in the nutritional knowledge of parents or caregivers of children with ASD and children without ASD. Methods: The research uses a case-control design with 102 samples (51 children with ASD and 51 children without ASD) obtained through cluster random sampling. Nutritional status data were collected from anthropometric measurements, dietary patterns through the SQ-FFQ, and parents' nutritional knowledge and children's diarrhea history through questionnaires. Data analysis utilized Independent Sample T-test or Mann Whitney tests. Results: Results showed significant differences in nutritional status (height-for-age, p-value=0.006), frequency of staple food consumption (p-value=0.018), animal protein (p-value=0.014), dairy products (p-value=0.001), amount of staple food consumption (p-value=0.016), dairy products (p-value=0.003), fat intake (p-value=0.037), fiber intake (p-value=0.033), frequency of diarrhea (p-value=0.042), and duration of diarrhea (p-value=0.042). However, there were no significant differences in BMI-for-age (p-value=0.410) and caregiver’s nutritional knowledge scores (p-value=0.855). Conclusions: It can be concluded that children with ASD and without ASD have differences in nutritional status, dietary patterns, and diarrhea history.